2022
DOI: 10.1002/slct.202201382
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Heterogeneous Photo‐Fenton‐Like Catalyst of e‐Fe2O3/SiO2/Attapulgite with Rich Oxygen Vacancies for Photocatalytic Degradation of Organic Pollutants

Abstract: Heterogeneous photo-Fenton oxidation is a promising solution to solve the problem of environmental pollution. Due to the low efficiency of the Fe 2 O 3 photo-Fenton catalyst, we loaded Fe 2 O 3 on the catalyst carrier of attapulgite (ATP) to obtain more active sites. Oxygen vacancies were introduced on the surface of the catalyst to improve the separation efficiency of photogenerated charges. The oxygen-vacancy-rich e-Fe 2 O 3 /SiO 2 /ATP Fenton-like photocatalyst was successfully synthesized by simple strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In contrast, there was scarce •OH radical signal for the α-Fe 2 O 3 sample vacuumed at a high temperature (573 K) owing to the removal of surface hydroxyl groups. Furthermore, the results of XPS (Table S1) and ESR (Figure S2) indicated that there was no discernible oxygen vacancy generation by the vacuuming and heat treatment in this experiment, 27,28 S3a), which is consistent with previous studies, which stated that the •OH radicals are primarily derived from H 2 O rather than O 2 . 29 In general, in the presence of water, •OH radicals can reconstitute to form H 2 O 2 in the aqueous phase through eq 1.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, there was scarce •OH radical signal for the α-Fe 2 O 3 sample vacuumed at a high temperature (573 K) owing to the removal of surface hydroxyl groups. Furthermore, the results of XPS (Table S1) and ESR (Figure S2) indicated that there was no discernible oxygen vacancy generation by the vacuuming and heat treatment in this experiment, 27,28 S3a), which is consistent with previous studies, which stated that the •OH radicals are primarily derived from H 2 O rather than O 2 . 29 In general, in the presence of water, •OH radicals can reconstitute to form H 2 O 2 in the aqueous phase through eq 1.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…In contrast, there was scarce •OH radical signal for the α-Fe 2 O 3 sample vacuumed at a high temperature (573 K) owing to the removal of surface hydroxyl groups. Furthermore, the results of XPS (Table S1) and ESR (Figure S2) indicated that there was no discernible oxygen vacancy generation by the vacuuming and heat treatment in this experiment, , excluding the possible influence of surface oxygen vacancy on •OH radical generation. These results demonstrated the important role of surface hydroxyl groups in the formation of •OH radicals on fresh α-Fe 2 O 3 samples.…”
Section: Resultsmentioning
confidence: 77%
“…To provide a comprehensive discussion on the role of the conductive carbon layer, and H 2 O 2 in the photocatalytic degradation of methyl orange, we also consider the photo-Fenton-like process and its impact on the reaction mechanism [21][22][23][24][25]. When H 2 O 2 is added to the photocatalytic system, it can enhance the degradation of organic pollutants by generating additional hydroxyl radicals (•OH) via a photo-Fenton-like reaction using H 2 O 2 and Fe(II/III) redox in the presence of light.…”
Section: Mechanism In Photocatalytic Degradationmentioning
confidence: 99%
“…The enhanced degradation can be attributed to the increased production of hydroxyl radicals through Fenton reaction involving H 2 O 2 and Fe ions. This suggests that both the photocatalytic process and the photo-Fenton-like process contribute synergistically to the degradation of methyl orange [21][22][23][24][25]. The concentration of H 2 O 2 and the initial pH of the solution were optimized to maximize the degradation efficiency.…”
Section: Mechanism In Photocatalytic Degradationmentioning
confidence: 99%
See 1 more Smart Citation